Drug toxicity of Levonorgestrel (LNGL) in Drosophila melanogaster targeting biochemical pathways - G, Swaroop; Annamati, Reshma; Viswanathan, Geetha; Radhakrishnan, Geethanjali; R, Poornima (International Journal of Pharmacology and Toxicology, 2013)
To achieve maximum contraceptive effectiveness Levonorgestrel tablets (LNGL) are taken exactly as directed and at intervals not exceeding 24 hours. The possibility of ovulation and conception prior to initiation of medication should be considered. Levonorgestrel pill was chosen for our research study since it is widely used by the people to be in command of the unwanted pregnancy and is the number one leading pill in the urban area throughout India. The cornerstone experimental animal in the study of cellular and molecular genetics for over 50 years has been the ubiquitous fruit fly (Drosophila melanogaster). Wheat’s cream media with different concentrations from 0.1mg to 3.0mg of LNGL was prepared to culture Oregon strain of Drosophila melanogaster. Proteins, Carbohydrates and Lipids were isolated and estimated to study the hamperness in the ecdysis of Drosophila melanogaster and also to find out the morphological and toxicological effect.  Results were encouraging us to go to the molecular level. Large amount of triglycerides were deposited in the abdomen of drosophila, protein concentration was more in experimental specimen than the control, and number of phenotypic variations were found with the flies treated with medicated LNGL media. “A survey was carried out on the consumption of Levonorgestrel pill in Bangalore urban area, India” in Gynaecology department at various hospitals in and around Bangalore, the symptoms seen in the subjects will be presented as evidential proof with respect to our research work.